2022
DOI: 10.3389/fpubh.2022.1002342
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of syphilis among people living with HIV and its implication for enhanced coinfection monitoring and management in China: A meta-analysis

Abstract: BackgroundPeople living with HIV (PLWH) are at an increased risk of syphilis infection. The objectives of this study were to assess the overall prevalence of syphilis among PLWH in China and identify factors associated with syphilis infection among PLWH.MethodsWe searched Medline, Embase, China National Knowledge Infrastructure (CNKI), Chinese Scientific Journals Database (VIP), Wan-fang Data, and Chinese Biomedical Literature Database (CBM) to identify studies that reported the prevalence of syphilis among PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 57 publications
1
8
1
Order By: Relevance
“…We found no significant difference in syphilis prevalence between male and female individuals living with HIV in sub-Saharan Africa, echoing the findings of a global pooled meta-analysis among the general population by Smolak et al 25 This result is, however, in contrast to findings from other settings where a higher syphilis prevalence has been reported among men versus women living with HIV 28–30 . Our pooled syphilis prevalence among pregnant women with HIV (7.0%; 95% CI, 5.8%–8.4%) was higher than in 2 systematic reviews and meta-analyses conducted among the general population of pregnant women in sub-Saharan Africa, both of which found a pooled syphilis prevalence of 2.9%.…”
Section: Discussionsupporting
confidence: 82%
“…We found no significant difference in syphilis prevalence between male and female individuals living with HIV in sub-Saharan Africa, echoing the findings of a global pooled meta-analysis among the general population by Smolak et al 25 This result is, however, in contrast to findings from other settings where a higher syphilis prevalence has been reported among men versus women living with HIV 28–30 . Our pooled syphilis prevalence among pregnant women with HIV (7.0%; 95% CI, 5.8%–8.4%) was higher than in 2 systematic reviews and meta-analyses conducted among the general population of pregnant women in sub-Saharan Africa, both of which found a pooled syphilis prevalence of 2.9%.…”
Section: Discussionsupporting
confidence: 82%
“…However, when comparing the prevalence of HIV/STD among African migrants with other high-risk groups such as men who have sex with men (HIV: 5.7%, syphilis: 5.8%) and attendees of STD clinics (NG: 11.95%, CT: 12.02%) in China, the prevalence among African migrants still remains relatively low [ 15 – 17 ]. We noticed that co-infection of HIV/STDs, such as HIV and syphilis, CT and NG, were reported frequently in other studies [ 18 , 19 ], while only one co-infection (CT and HBsAg) has been observed in our study. The limited sample size of our study may lead to this discrepancy, and other potential associated factors were needed to explore in further research.…”
Section: Discussioncontrasting
confidence: 46%
“…This study assessed the prevalence of current syphilis infection among virally suppressed PLWH in Zhejiang Province, China, in 2022. According to national reporting data, the annual incidence of primary and secondary syphilis have decreased from 13.44% in 2012 to 9.81% in 2015 ( 28 ), and the overall prevalence of syphilis among PLWH in China was 19.9% ( 29 ). Furthermore, according to 2011 global statistics, the mean prevalence of syphilis among PLWH was 9.5% ( 30 ).…”
Section: Discussionmentioning
confidence: 99%